Approaches to determine the ultimate strength and failure mechanisms of RC short columns retrofitted by FRP. Issue 11 (2nd November 2018) - Le Nguyen, K.; Brun, M.; Limam, A.; Ferrier, E.
Abstract : In the context of building protection against earthquakes, the strengthening technique by FRP (Fibre-Reinforced Polymers) plating and wrapping provides a relevant solution. The objective of this research is to evaluate the ultimate strength and failure mechanisms of externally FRP retrofitting on RC short columns. The analytical approach employs design equations proposed in construction guidelines for reproducing the concrete confinement provided by FRP wraps with fibres predominantly in the hoop direction. The strength and failure modes provided by the analytical approach are consistent with the experimental data. Then, a pushover analysis using a finite-element method is performed to investigate the efficiency for the FRP-retrofitted configurations of the short RC columns. The numerical assessment of the shear strength turns out to be more accurate than the one issued from analytical approach. In addition, the observed failure modes are well retrieved and are clearly illustrated through the display of consistent bending or shear cracking patterns. Finally, the ultimate displacements are assessed by the numerical procedure, highlighting the advantages of the partially FRP-strengthened configuration in comparison to the fully strengthened case in terms of ductility.